Red blood cell profile of elite olympic distance triathletes. A three-year follow-up - Rietjens, G. J.; Kuipers, H.; Hartgens, F.; Keizer, H. A. (International Journal of Sports Medicine, 2002)
The purpose of this study was to monitor general and individual changes in hematological variables during long-term endurance training, detraining and altitude training in elite Olympic distance triathletes. Over a period of three years, a total of 102 blood samples were collected in eleven (7-male and 4 female) elite Olympic distance triathletes (mean +/- SD; age = 26.4 +/- 5.1yr; Vdot;O 2 max = 67.9 +/- 6.6 ml/min/kg) for determination of hemoglobin (Hb), hematocrit (Hct), red blood cell count (RBC), Mean corpuscular hemoglobin (MCH), Mean corpuscular hemoglobin content (MCHC), Mean corpuscular volume (MCV) and plasma ferritin. The data were pooled and divided into three periods; off-season, training season and race season. Blood samples obtained before and after altitude training were analyzed separately. Of all measured variables only RBC showed a significant decrease (p < 0.05) during the race season compared to the training season. Hematological values below the lower limit of the normal range were found in 46 % of the athletes during the off-season. This percentage increased from 55 % during the training season to 72 % of the athletes during the race season. Hemoglobin and ferritin values were most frequently below the normal range. There was a weak correlation between Hb levels and Vdot;O 2 max obtained during maximal cycling (r = 0.084) and running (r = 0.137) tests. Unlike training at 1500 m and 1850 m, training at an altitude of 2600 m for three weeks showed significant increases in Hb (+ 10 %; p < 0.05), Hct (+ 11 %; p < 0.05) and MCV (+ 5 %; p < 0.05). Long-term endurance training does not largely alter hematological status. However, regular screening of hematological variables is desirable as many athletes have values near or below the lower limit of the normal range. The data obtained from altitude training suggest that a minimum altitude (>2000 m) is necessary to alter hematological status.